Assorted morphosynthesis: access to multi-faceted nano-architectures from a super-responsive dual π-functional amphiphilic construct. Issue 83 (21st July 2015) - Asthana, Deepak; Shukla, Jyoti; Dana, Srikanta; Rani, Varsha; Ajayakumar, M. R.; Rawat, Kamla; Mandal, Kalyanashis; Yadav, Premlata; Ghosh, Subhasis; Mukhopadhyay, Pritam
Abstract : An electronically segmented amphiphile was created by conjugating two π-functional units (HQ/NDI) for the first time. Abstract : An electronically segmented amphiphile was created by conjugating two π-functional units hydroxyquinoline and naphthalenediimide (HQ/NDI) for the first time. The differential electrostatic potential of the π-surfaces, H-bonding units, etc. trigger a manifold response and direct the assembly of a unique collection of seven diverse nano-architectures. Chiral assembly, distinct classes of fibers, 3-D sheets, and metallo-spheres/fibrils with μM levels of Co/Cu/Zn(ii ) ions emerged from this new approach of assorted morphosynthesis under ambient conditions.